Chaotic elliptic map for speech encryption - Obaida M. Al-hazaimeh; Ashraf A. Abu-Ein; Khalid M. Nahar; Isra S. Al-Qasrawi (Institute of Advanced Engineering and Science, 2022)
Using a new key management system and Jacobian elliptic map, a new speech encryption scheme has been developed for secure speech communication data. Jacobian elliptic map-based speech encryption has been developed as a novel method to improve the existing speech encryption methods' drawbacks, such as poor quality in decrypted signals, residual intelligibility, high computational complexity, and low-key space. Using the Jacobian elliptic map as a key management solution, a new cryptosystem was created. The proposed scheme's performance is evaluated using spectrogram analysis, histogram analysis, key space analysis, correlation analysis, key sensitivity analysis and randomness test analysis. Using the results, we can conclude that the proposed speech encryption scheme provides a better security system with robust decryption quality.